DESCRIPTION OF KNOWLEDGE ABOUT THE IMPORTANCE OF FRUIT AND VEGETABLE CONSUMPTION IN SCHOOL AGE CHILDREN IN RENA PANJANG VILLAGE IN 2021 - Oshi Famela Chandry; Miratul Haya; Ayu Pravita Sari (Jurnal Vokasi Keperawatan (JVK), 2021)
According to 2018 Riskesdas data, 95.5% of Indonesians aged ?5 years are in the category of less fruit and vegetable consumption. Bengkulu Province shows that the proportion of the population aged ?5 years who does not consume fruits and vegetables reaches 94%. Seluma district is included in the category of less fruit and vegetable consumption.This research is descriptive with quantitative methods which aims to describe the knowledge of school-age children in Rena Panjang Village in 2021. The population in this study amounted to 52 people. Sampling in this study was taken by non-random sampling with purposive sampling method (sampling based on certain considerations that have been made by the researcher) with a total sample of 52 samples. Data collection was carried out by filling out a questionnaire. Data processing was done manually and computerized with steps of editing, coding, entry, cleaning and tabulating. The data analysis used is descriptive analysis using percentages.The results showed that most of them had poor knowledge about the importance of fruit consumption as much as 59.61% (31 respondents), adequate knowledge as much as 32.69% (17 respondents) and good knowledge as much as 7.69% (4 respondents). Most of them have poor knowledge about the importance of vegetable consumption as much as 36.53% (19 respondents), sufficient knowledge as much as 30.76% (16 respondents) and good knowledge as much as 32.69% (17 respondents). It is suggested to the community or parents or health workers who are in the working area of the district to increase their active role in providing information or health education to children about the importance of fruit and vegetable consumption, such as holding counseling or distributing brochures and leaflets.